(3JMQjQ cJGH eGfGdGhS aj GdCTcGd GdcQjIs - (3eGfGdGhSs
(3ChdgG (B:s
(3Efi cfJ CQjO Cf CMQQ GdcJH GdehSheI HGdeJhSWGJ CYfi GdcJH GdJi ef TCfgG Cf JJhSW ai GdJQJjH GdJYdjei Hjf cJGH GdCUhd CbdjOS Hjf cJGH GdeLSWi GdHWdjhSi s
(3BNQgG (B:s
(3bhdg ai BNQ GdcdGe heJi cGfJ Q VdY eQHY C h H VdY eQHY hgPG BNQ GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeSs
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B143s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdQjGVjGJs